Postbooster Antibodies from Humans as Source of Diphtheria Antitoxin - Jesús F. Bermejo-Martin (Emerging Infectious Diseases, 2016)
Diphtheria antitoxin for therapeutic use is in limited supply. A potential source might be affinity-purified antibodies originally derived from plasma of adults who received a booster dose of a vaccine containing diphtheria toxoid. These antibodies might be useful for treating even severe cases of diphtheria.